Peran Ambidexterity Organisasi Sebagai Variabel Intervening Dalam Meningkatkan Kinerja Pemasaran UMKM Di Masa Covid-19 - Wendi Nurwendi; Didit Haryadi (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
Micro, small and medium enterprises (MSMEs) explore new opportunities to gain profits and optimize existing resources. The presence of operational ambidexterity can focus on exploiting existing resources and exploring market opportunities. This study shows the influence of factors that can improve MSME marketing performance by adjusting product innovation strategies and customer orientation through ambidexterity during the covid-19 pandemic. The population of this research is MSME food and beverage in Serang, totalling 1,858 MSMEs. The number of samples is 170 respondents with the purposive sampling method. The analysis method uses a structural equation model (SEM) approach with the SmartPLS applications. The results showed that product innovation, market orientation, and organizational ambidexterity positively and significantly affected marketing performance. Product innovation and market orientation positively and significantly affected organizational ambidexterity. Organizational ambidexterity can mediate the effect of product innovation and market orientation on marketing performance. The results of this study can complement the existing theory. Then the results of this study can also be used as a reference for MSMEs in improving marketing performance by increasing product innovation and market orientation directly or through organizational ambidexterity.